The Effectiveness of Emotion-Focused Couples Therapy on Marital Commitment, Love Schemas, and Emotional Schemas in Couples with Extramarital Affairs - Isari, Saeed; Shahbazi, Masoud; Gholamzadeh Jofreh, Maryam (Applied Family Therapy Journal (AFTJ), 2024)
Objective:  The aim of this study was to examine the effectiveness of Emotion-Focused Couples Therapy (EFCT) on marital commitment, love schemas, and emotional schemas in couples with extramarital affairs.Methods: This research employed a semi-experimental single-case design with a multiple baseline method. The statistical population of this study included all couples with experience of extramarital affairs who referred to family courts and the prevention unit of the welfare organization in Dezful city in the year 2022. A total of 4 couples (8 individuals) were selected through purposeful sampling. The EFCT process was conducted in three baseline stages, across 8 sessions of 90 minutes each, with a two-month follow-up. Participants responded to the Marital Commitment Questionnaire by Adams and Jones (1997), the Love Schema Questionnaire by Yarahmadi-Vaseli et al. (2020), and the Leahy Emotional Schema Scale (LES) (2002). Data were analyzed using visual inspection, reliable change index, and percentage improvement formula.Findings: The results indicated that EFCT led to an increase in marital commitment in couples with extramarital affairs (P